(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Materials and Methods: In Blockchain technology, security, stability (immutability), and decentralization are among the important things that make this technology useful in various areas of life that serve the user. These advantages were used to solve many problems facing the network, including those of productivity, processing time, and scalability. Various methods were used in the solution, including working on a change in the network structure, choosing a basic node (the manager), parallel mining, and competing with other miners. Results: Through recent studies, it has been shown that the Blockchain technology has been used in various fields, as it is characterized by many advantages, the most important of which are security, decentralization, and stability. Because of these advantages, it outperforms other technologies. Conclusion: Due to its advantages, the tendency to use blockchain technology has increased in many fields, including financial, agricultural, commercial, health, the Internet of Things, and others. It includes decentralization, distribution, reliability, and stability. There are other trends that have worked to improve the performance, efficiency, and security of the blockchain system itself, In the Internet of Things, healthcare, supply chain management, the banking sector, and digital marketing In addition to studies that include improving the efficiency, security, and development of the system.